Corneal Graft in Children - Syed Fawad Rizvi, Munira Shakir, Syeda Aisha Bokhari, Shakir Zafar, Zeeshan Kamil (Pakistan Journal of Ophthalmology, 2012)
Purpose: To share our experience of penetrating keratoplasty in children at a tertiary care hospital. Material and Methods: In this study, records of pediatric keratoplasty performed on 90 eyes in 85 children of less than 14 years of age at the Pediatric Department of LRBT Free Base Eye Hospital Karachi, for the period of 3 years from January 2006 to December 2008 were reviewed. Results: Out of 85 patients, 45 (52.94%) were boys and 40 (47.05%) were girls. Indications were scarring after keratitis in 16 (17.7%) eyes, traumatic corneal scarring in 16 (17.7%), corneal dystrophies 22 (24.4%), keratoconus and hydrops in 26 (28.8%), chemical injury in 8 (8.8%) and congenital glaucoma in 2 (2.2%). Total 65 out of 90 (72%) eyes showed clear cornea at final follow up. Grafts performed for keratoconus were the most successful in terms of graft survival, which accounted for 23 out of 26 (88.46%) eyes. Improvement in visual acuity was recorded in 64 out of 90 (71.11%) eyes. Best corrected visual acuity of 6/24 or better was achieved in 22 out of 90 (24.44%) patients. Conclusion: In conclusion, our experience of keratoplasty in pediatric age group yielded promising results.